THE EFFECT OF PROGRAM APPLYING PENDER’S HEALTH PROMOTION MODEL WITH QUALITY OF LIFE AMONG THE ELDERLY CHOK CHAI SUB-DISTRICT MUNICIPALITY, CHOK CHAI DISTRICT, NAKHON RATCHASIMA PROVINCE - ดีสุด , สุเทพ; เพชรมณี, สาโรจน์; ปัญญาใสโสภณ, ธณกร (Primary Health Care Journal (Northeastern Edition), 2024)
This quasi-experimental study aimed to examine the effect of a program applying Pender’s Health Promotion Model on the quality of life among elderly individuals in Chok Chai Sub-District Municipality, Chok Chai District, Nakhon Ratchasima Province. The participants were divided into two groups. The experimental group, consisting of 30 individuals, received the program based on Pender’s Health Promotion Model, while the control group, also comprising 30 individuals, received the standard health promotion program. Participants were selected through simple random sampling. The instruments included the program applying Pender’s Health Promotion Model and the World Health Organization Quality of Life Questionnaire. Data analysis involved frequencies, percentages, means, standard deviations, paired samples t-tests, and independent samples t-tests. The results showed that after receiving the program, the experimental group demonstrated significantly improved quality of life, including physical, psychological, social, and environmental dimensions, compared to their baseline and the control group (p-value < .01). In conclusion, the development of the quality of life among the elderly should involve a comprehensive assessment prior to implementation. Interventions should promote activities that enhance overall quality of life and its specific dimensions, emphasizing the integration of activities tailored to the local context.